Is There a Place for Philosophy in the Social Sciences? - Kirtiklis, Kęstutis (Sociologija. Mintis ir veiksmas, 2010)
The article deals with the problem of relationship between social sciences and philosophy. In contemporary social sciences this relationship is denied by not ascribing to philosophy the status of autonomous discipline, which could be considered as being separate from social sciences and yet fruitfully collaborate with them. The positivist tradition of the social sciences denies the importance philosophy, considering it as a merely speculative enterprise, which is not worthy of attention of social scientists oriented towards the increase of empirically verified scientific knowledge. On the other hand, the interpretive tradition of the social sciences tends to incorporate philosophy into social sciences as an integral part of social theory. However, claims the author, the divide into two traditions itself shows the importance of philosophy, since both of these traditions already depend on the philosophical presuppositions of their exponents. The article argues that philosophy of social sciences should be considered as a separate and autonomous discipline, because of the objects it studies and the methods it uses, which differ from those of social sciences. However philosophy can (and actually does) fruitfully collaborate with social sciences by formulating their methodological basis.